The quality of peanut chocolate bar processed in Barangay Bubog, Talisay, Negros Occidental - Tan, Christine Cristoria
The quality of peanut chocolate bar, produced by a small-scale food processor in Barangay Bubog, Talisay, Negros Occidental, was evaluated and established.